Preventive Maintenance Study on H-25 Gas Turbine - Sulaiman; Fahmirullah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
This study aims to determine the effect of the time-based maintenance method preventive maintenance, namely major inspection on the efficiency of H-25 gas turbine. The efficiency calculation method based on operating data from the gas turbine. The effect of major inspection can be seen from the compressor efficiency, turbine efficiency and fuel consumption. The results of calculations before the major inspection are 80% of compressor efficiency, 83% of turbine efficiency, and 0.751 kg/kWh of fuel consumption, while after the major inspection, compressor efficiency is 80%, turbine efficiency is 85% and fuel consumption is 0.740 kg/kWh.